2020
DOI: 10.1093/nar/gkaa507
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of an atypical cobalamin riboswitch reveals RNA structural adaptability as basis for promiscuous ligand binding

Abstract: Cobalamin riboswitches encompass a structurally diverse group of cis-acting, gene regulatory elements found mostly in bacterial messenger RNA and are classified into subtypes based on secondary and tertiary characteristics. An unusual variant of the cobalamin riboswitch with predicted structural features was identified in Bacillus subtilis over a decade ago, but its structure and mechanisms of cobalamin selectivity and translational control have remained unsolved. We present the crystal structure of the aptame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 52 publications
2
46
2
Order By: Relevance
“…Notably, deletion of btuR, which encodes the adensosyltransferase that installs the Ado upper ligand group, rendered the B. subtilis btuF Cbl-riboswitch reporter insensitive to exogenously supplied CNCbl, MeCbl, and OHCbl, while retaining dose-dependent repression in response to AdoCbl (Figure S1). This strongly suggests that the B. subtilis btuF Cbl-riboswitch only responds to Cbl containing the 5'-deoxyadenosine upper ligand, in contrast with a report suggesting that this riboswitch aptamer can also bind MeCbl and OHCbl (Chan and Mondragón, 2020).…”
Section: Experimental Strategy -Development Of An In Vivo Reporter Sy...contrasting
confidence: 79%
See 2 more Smart Citations
“…Notably, deletion of btuR, which encodes the adensosyltransferase that installs the Ado upper ligand group, rendered the B. subtilis btuF Cbl-riboswitch reporter insensitive to exogenously supplied CNCbl, MeCbl, and OHCbl, while retaining dose-dependent repression in response to AdoCbl (Figure S1). This strongly suggests that the B. subtilis btuF Cbl-riboswitch only responds to Cbl containing the 5'-deoxyadenosine upper ligand, in contrast with a report suggesting that this riboswitch aptamer can also bind MeCbl and OHCbl (Chan and Mondragón, 2020).…”
Section: Experimental Strategy -Development Of An In Vivo Reporter Sy...contrasting
confidence: 79%
“…These structural models show that the base-on tails are contained within the binding site, whereas the tails of the base-off Cbl structures protrude away from the binding site and clash with the L5-L13 kissing loop. Although the B. subtilis btuF (Figure S8C-D) and Symbiobacterium thermophilum cblT (Figure S8E-F) riboswitch models do not contain the L13 structure of the kissing loop, some of the modeled base-off tails clash with L5 of the aptamer in these structures (Chan and Mondragón, 2020; Peselis and Serganov, 2013). The kissing loop has been shown to play a key mechanistic role of sensing the corrinoid-binding state of the aptamer domain to influence downstream regulatory structures in the expression platform (Lussier et al, 2015; Polaski et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystal structures of riboswitches often show one or more magnesium ions bound to the RNA (Huang and Lilley 2018;C. Lu et al 2010;Chan and Mondragón 2020;Furukawa et al 2015) though in some cases these ions can be found in unexpected locations or even absent (Gilbert et al 2008;Garst et al 2008) despite the clear evidence that these riboswitches undergo structural changes in the presence of these ions (Chen et al 2012;Garst et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The number of magnesium ions that interact with the RNA and the affinity of the RNA to these ions are variable [5,11]. Crystal structures of riboswitches often show one or more magnesium ions bound to the RNA [2,[11][12][13] though in some cases these ions can be found in unexpected locations or even absent [14,15] despite the clear evidence that these riboswitches undergo structural changes in the presence of these ions [7,15].…”
Section: Introductionmentioning
confidence: 99%